Pengenaan Pidana bagi Saksi Pemberi Keterangan Palsu dalam Sistem Hukum Pidana - Yudi Yudi; Nourma Nourma; Firstnandiar Firstnandiar (CV Rewang Rencang, 2025)
One of the problems in the judicial system is the provision of false testimony in court. This not only hinders the process of investigating the truth but can also be detrimental to the parties involved, including undermining public trust in the judicial system. Therefore, a witness in a criminal case is required to report what they saw, knew, and heard under oath. The purpose of the trial is to discover the material truth, that is, the truth that actually occurred, in order to achieve justice. As stipulated in Article 242 of the Criminal Code, this act is a criminal offense. In addition to being repressive, enforcing criminal penalties against witnesses who provide false testimony is evidence of an effort to uphold the law and maintain the integrity of the judicial process. The method used is descriptive with a normative juridical research approach. If a witness is proven to have given false testimony, they will be subject to criminal penalties as stipulated in the Criminal Code. Therefore, it is crucial in a trial process to present witnesses whose testimony is credible and whose testimony is believed to be truthful.